PEMBUATAN DAN PENGADAAN BIOPORI SEDERHANA SEBAGAI UPAYA PENINGKATAN LAJU INFILTRASI DAN CADANGAN AIR TANAH - Amalia, Novira Dwi; Basri, Hasan; Putrianika, Puput; Desty Widyowati, Dian (Universitas Islam 45 Bekasi, 2024)
The increasing demand for water each year necessitates conservation efforts, particularly for groundwater resources. One effective method is the implementation of biopore infiltration holes as a strategy to enhance infiltration rates and groundwater storage capacity. This community service program aims to provide training on the construction of simple biopores for residents of Ridogalih Village, Cibarusah District, Bekasi Regency. The program includes awareness sessions on the significance of biopores in maintaining the hydrological cycle balance, as well as hands-on training in their construction and maintenance. Through this initiative, it is expected that the community will independently adopt biopore technology to enhance rainwater absorption and mitigate surface water stagnation or flooding. The results of the program indicate a significant improvement in the participants’ understanding and skills regarding the benefits and implementation of biopores. Participants not only grasped the fundamental concepts of biopores but also demonstrated the ability to apply them within their surroundings. The positive impacts of this initiative include an increased infiltration rate, reduced surface runoff, and improved groundwater reserves, contributing to better water availability for the community. The sustainability of this program is expected to encourage active community participation in environmental conservation and serve as a model for other regions facing similar challenges in water resource management.